The Adoption and Use of Moodle in Online Learning: A Systematic Review - Mustafa A.S.; Ali N. (Natural Sciences Publishing, 2024)
The rapid evolution of ICT has enabled several institutions to adopt Moodle as their preferred e-learning platform. Moodle is increasingly being used for interactive, personalised, and collaborative learning and improving online assessments. Despite Moodle's increasing popularity, there are limited reviews on the empirical evidence of its efficacy among students. The study aimed to provide an overview of the scientific literature on the studies that investigated the behavioural intention and actual usage of Moodle. This review shows that Moodle is mainly used in universities and effectively improves student performance, attitude, and satisfaction. Most studies that applied a theoretical ground applied the Technology Acceptance Model (TAM). Meanwhile, performance expectancy, effort expectancy, facilitating condition, perceived usefulness of professors, perceived ease of use, and subjective norms are essential drivers for online learning systems' acceptance or actual usage. These findings serve as evidence and reference for educational institutions in developing online learning policies and strategies. Further studies need to incorporate behavioural and motivational theories when designing Moodle courses. 2023 NSP.